PENGUATAN NILAI-NILAI PANCASILA, TOLERANSI DAN PENDIDIKAN POLITIK DI DESA PESANGGRAHAN KABUPATEN MOJOKERTO JAWA TIMUR - Mi’rojul Huda; Muhammad Farid Ilhamuddin, Rahmanu Wijaya, Wahyudi, Rianda Usmi (JOURNAL OF COMMUNITY DEDICATION, 2023)
In facing the nation's challenges, Indonesia needs to reactualize the values of Pancasila, which have proven to be a solution to national problems. Pancasila, as the foundation of the Indonesian state, plays a crucial role in providing solutions to various national issues, including the issue of intolerance. Unfortunately, the values of Pancasila are increasingly eroded, as seen in the lack of knowledge, attitudes, and behaviors exhibited by the society in daily life. Actions that should not be taken emerge, triggering various disputes, hostilities, and divisions. Pancasila has faced various challenges and historical dynamics in the political system, ranging from the era of parliamentary democracy, guided democracy, the New Order era, to the era of multiparty democracy during the reform period. The Pancasila ideology is also built on the inherent diversity of the Indonesian nation. Indonesia is known for its wealth of natural resources, ethnic diversity, religions, beliefs, and cultures. The diversity of society in terms of social order, religion, and ethnicity has existed since ancient times. The coexistence of diverse cultures is a wealth in the national cultural heritage.